2019
DOI: 10.1002/jcp.28463
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations and haplotypes in the annexin A5 gene are associated with the risk of recurrent pregnancy loss

Abstract: The expression of annexin A5 (ANXA5) was shown to affect the pathogenesis of recurrent pregnancy loss (RPL). In this study, the effects of two haplotypes, M1 and M2, on the transcription efficiency of ANXA5 promoter were explored. Correlation analysis was used to investigate the association between the single‐nucleotide polymorphism haplotypes in ANXA5 promoter and the risk of RPL. And a luciferase reporter assay was carried out to study the effects of haplotypes M1 and M2 on the transcription efficiency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies have suggested that ANXA5 is related to RSA (22)(23)(24)(25). Lan et al found that reduced ANXA5 expression was associated with a higher risk of RSA (26). Furthermore, the haplotype in the proximal core promoter region of ANXA5 gene, including rs28717001, rs112782763, rs113588187, and rs28651243, is associated with URSA (23).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that ANXA5 is related to RSA (22)(23)(24)(25). Lan et al found that reduced ANXA5 expression was associated with a higher risk of RSA (26). Furthermore, the haplotype in the proximal core promoter region of ANXA5 gene, including rs28717001, rs112782763, rs113588187, and rs28651243, is associated with URSA (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a close relationship between the M2 haplotype and the occurrence of pre-eclampsia and gestational disorders, while the susceptibility to FGR is increased by M2 haplotype (29,30). It has also been shown that the activity of ANXA5 promoter in placental tissue samples harvested from patients with RPL was markedly reduced to decrease Anxa5 expression, suggesting that the M2 haplotype increased RPL risk by reducing the expression of Anxa5 (31). In the present study, the luciferase assays demonstrated that the M2 haplotype was responsible for the transcription efficiency of the ANXA5 promoter.…”
Section: Discussionmentioning
confidence: 99%